Implementasi Good Govermance Dalam Proses Transfer Aset Pemerintah Daerah Kota Sumedang - Maulana, Arman; Rosmayati, Siti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The method used in this study is a qualitative method according to Usman (2009: 78) qualitative method ismore based on phenomenological philosophy that prioritizes appreciation (verstehen). The qualitativemethod seeks to understand and interpret the meaning of an event of human behavior interaction in aparticular situation according to the researchers' own perspective where respondents in the skinativemethod develop (snowball) in a purposeful manner (perposive) until the data collected is consideredsatisfactory. As described above, the methodology used is a descriptive qualitative approach so that thefocus of research focuses on existing problems or the actual problem of the Sumedang City Governmentand West Java Province, namely, Analyzing the implementation of good governance in the process oftransferring assets of the Sumedang City Government which aims to optimize the potential assets. Theimplementation of good governance uses 4 (four) main principles, namely the principle of accountability,the principle of role of law, the principle of transparency, and the principle of community participation,taking into account the application of asset management. According to Sutopo and Arief (2010: 4).Qualitative data is in the form of descriptive form, in the form of verbal or written words about observablehuman behavior. The qualitative data took the form of detailed descriptions, direct quotes, and casedocumentation, this data was collected as a respondent's story, without trying to match a phenomenon withpredetermined predefined categories as the answer to the question. 1. The inventory of BPKAD assets inSumedang Regency has been carried out in all BPKAD units and routinely every year. At BPKAD the HeadOffice of asset inventory is carried out by the Staff of the Field of Asset Registration and the Staff of theField Accounting Office.